Concepts and methodologies for a new relational geography of energy demand: Social practices, doing-places and settings. (February 2018) - Hui, Allison; Walker, Gordon
Abstract: Understandings of space as not an objective surface or container but rather a set of relations that are continually made and re-made have become well established within the social sciences, yet they remain noticeably absent in how energy demand research is understood and undertaken. This is, in part, because relevant vocabularies and methodologies remain minimally developed. This paper therefore establishes a conceptual approach, vocabulary and set of methodologies that offer new opportunities for understanding the spatial deployment of energy. In doing so, it works at the intersection of energy geographies and theories of practice, engaging in particular with the concepts of place, anchors and settings from Schatzki's site ontology. After introducing these concepts, the paper outlines how they can provide a more conceptually sophisticated understanding of the energy demand dynamics of a range of changing social practices. It then presents methodologies capable of foregrounding the relational spatialities of practice and energy demand. It argues that carefully working through how energy demand arises as a consequence of social practices, and how spatialities of practice matter for understanding energy service provisioning, helps in developing methodologies that push energy research into refreshingly unfamiliar explorations, analyses and strategies for addressing associated challenges.